Policy of providing open-access e-books at LIPI during the Covid-19 pandemic - Muhammad Fadly Suhendra; Laksmi Laksmi (Jurnal Kajian Informasi dan Perpustakaan, 2022)
The policy of providing open-access e-books is one form of information disclosure carried out by LIPI in building a public facility in the form of a credible and innovative source of scientific literacy, particularly related to scientific publications of publicly funded research results. This research analyzed the policy of providing LIPI e-books in 2020-2021 in the Covid-19 pandemic. This study used a qualitative approach with a case study method. Data collection was carried out in May-June 2021 through in-depth interviews with two informants, a literature review, and observation of document searches related to the policy of providing open-access e-books at LIPI Press. The results indicated that the policy was fulfilled by implementing the Local Knowledge Acquisition Program and the Open Monograph Press (OMP) electronic publishing system. This policy has effectively increased the visibility, accessibility, and usefulness of scientific books during the Covid-19 pandemic. This can be seen from the increasing number of access to LIPI Press e-books provided through OMP throughout 2020-2021. However, the lack of understanding of open access among the public is a challenge in providing e-books. At the same time, the limited number of human resources who handle the electronic publishing information technology system is a fundamental problem in developing an e-book publishing system. This study concludes that the basis and implementation of the policy for providing open-access e-books are feasible to be maintained and improved, especially as a form of accountability for public funds used for public knowledge sources.